Computed tomography evaluation of the liver and gallbladder in domestic cats (Felis catus domesticus) Parasitized by platynosomum illiciens (braun 1901) kossak 1910 - Azevedo, Felipe Delorme; Da Veiga, Cristiano Chaves Pessoa; Scott, Fábio Barbour; Azevedo, Thais Ribeiro Correia; De Souza, Bruno Gonçalves; Vulcano, Luis Carlos [UNESP] (My University, 2012)
Platynosomum illiciens (Braun 1901) Kossack, 1910, is the most important trematode found in cats, and its prevalence can reach up to 85%. Due to the P. illiciens diagnosis is being done exclusively through the eggs presence of this parasite by fecal examination, and this is considered being little sensible, it is necessary the study of complementary tools of diagnosis for the parasite and the hepatic alterations possibly determined by this parasite. Therefore, computed tomography were used for the evaluation of alterations caused by P. illiciens in order to evidence alterations that aid in the diagnosis of this parasitosis or even to evidenced alterations caused by the platynosomiasis. Seven positive cats were found, and submitted to compute tomography. Six cats were observed with enlargement of the liver and in regard to the other findings the results were descriptive. The computed tomography were considered good diagnostic tools, evaluating with clarity the hepatic size, the hepatic parenchyma, the configuration and width of bile ducts, the gall bladder and the hepatic vessels.
Keywords: Feline; Image diagnosis; Liver fluck